Probing the Electrochemical Reaction Mechanism and Crystallinity Effect of RuO2 for Sodium Storage. Issue 11 (7th September 2018) - Lu, Fan; Liu, Shengzhou; Zeng, Guifan; Li, Jumei; Yang, Yin
Abstract : Sodium ion batteries (SIBs) have received dramatically increasing research interests in the last few years owing to the natural abundance and wide distribution of Na resources worldwidely, promising their huge potential in large-scale energy storage technologies. Anode materials, as one of the key components determining SIB performance, are still far away from meeting expectations of high-performance SIBs. Therefore, more advanced materials urgently need to be explored as SIB anodes and their working mechanisms require investigation. To this end, RuO2, a model electrode material for lithium ion battery (LIB) and supercapacitor, is employed as anode for rechargeable SIB for the first time. It is found that the crystallinity of RuO2 plays a critical role in determining the electrochemical performance. The sample synthesized by annealing the amorphous-like RuO2 at 500°C presents the best performance in terms of initial coulumbic efficiency, capacity, cycling stability and rate capability. It is worthy emphasizing that the optimized RuO2 sample presents initial coulumbic efficiency of 80% and delivers a capacity of 255 mAh g −1 at extremely large current density of 4030 mA g −1, which are leading the performance in metal oxide anodes for SIBs. In addition, the electrochemical reaction mechanism of RuO2 with Na is investigated by ex-situ XRD technique. We propose that, for the first time, crystalline RuO2 react with Na to generate amorphous Ru/Na2 O mixture during initial discharge process. Upon charging, the Ru/Na2 O mixture converts to amorphous RuO2 . As for the subsequent cycles, the conversion reaction between amorphous RuO2 and Ru/Na2 O sustains the RuO2 /Na cell working. The findings in this study provides a new valuable anode for high-performance SIBs and an insightful point of optimizing electrochemical performance by controlling the material's crystallinity.